A novel control strategy for Reflex-based electric vehicle charging station with grid support functionality. (August 2017) - Bayati, Mahdi; Abedi, Mehrdad; Hosseinian, Hossein; Gharehpetian, Gevork B.
Abstract : Highlights: Reflex method has distinct advantages compared to other bulk charging methods. A reflex-based fast charging station for electric vehicles has been designed. Reflex method leads to a power quality problem. A novel control strategy has been proposed to avoid the power quality problem. Finally, some crucial factors for design of a desired station have been discussed. Abstract: This paper proposes a novel control strategy for a charging station which provides reflex-based fast charging service for electric vehicles through a number of connection ports. Reflex method has distinct advantages compared to other bulk charging methods. It applies a three-stage charge sequence, a positive, negative, and zero battery current for each cycle. Due to uninterrupted drastic changes in the battery currents during the cycles of this method, the charging station encounters an important power quality issue in which phasor of the AC-side terminal current changes significantly and level of the delivered power to the batteries has considerable variations. An ultra-capacitor is connected to it according to a particular topology and then, is controlled according to the novel control strategy in order to resolve the power quality problem.